FIRM SIZE IN MODERATING ESG PERFORMANCE AND FIRM VALUE IN INDONESIA - Christian Adventus; Zicry Denni Mahardika; Rafly Ade Setyawan; Risal (Universitas Tulungagung, 2026)
This research investigates how Environmental, Social, and Governance (ESG) metrics influence corporate worth within the Indonesian business landscape, while exploring corporate scale as a contextual moderator. Adopting a quantitative methodology, sample selection focused on enterprises registered on the Indonesia Stock Exchange (IDX) between 2017 and 2021 using specific purposive criteria. Corporate valuation was quantified through Tobin’s Q, sustainability disclosures were retrieved from ESG Intelligence, and organizational size was captured via market capitalization values. Statistical processing was executed through Moderated Regression Analysis (MRA). The data reveal that ESG compliance exerts a significantly positive effect on corporate worth, demonstrating that executing sustainable, ecofriendly, and socially responsible operations effectively boosts market standing. Moreover, structural moderation analytics confirm that company scale heavily interacts with this linkage, amplifying the favorable impact of sustainability initiatives on valuation metrics. This indicates that the rewards of ESG integration are substantially more evident in larger enterprises, driven by their extensive resource capabilities and intensified scrutiny from external stakeholders. These outcomes align with stakeholder theory, reinforcing that embedding ethical standards into corporate blueprints delivers sustainable competitive edges and protects corporate longevity.